(untitled) (Global Journal of Management and Business Research, 2024)
This study uses primary data from a survey of 370 observations in Ho Chi Minh City Vietnam and adopts the Exploratory Factor Analysis Confirmatory Factor Analysis CFA and Linear Regression Modeling LRM with Bootstrap analysis for a reliable test of LRM Its result shows that factors affecting Seaport competitiveness included Geographical Location Connectivity Information Technology Facilities Reputation and Port authority